2008
DOI: 10.1534/genetics.107.083691
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Analysis of the N-Acylsphingosine Amidohydrolase Gene Associated With Mental Activity in Humans

Abstract: To understand the evolution of human mental activity, we performed population genetic analyses of nucleotide sequences ($11 kb) from a worldwide sample of 60 chromosomes of the N-acylsphingosine amidohydrolase (ASAH1) gene. ASAH1 hydrolyzes ceramides and regulates neuronal development, and its deficiency often results in mental retardation. In the region ($4.4 kb) encompassing exons 3 and 4 of this gene, two distinct lineages (V and M) have been segregating in the human population for 2.4 6 0.4 million years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 76 publications
0
9
1
Order By: Relevance
“…Nonetheless, introgression and selection are not mutually exclusive, as a haplotype introduced by admixture may have higher chances to be detected in modern populations when subjected to a selective event (that opposes its chances of being lost by drift). This has been shown to be the case for other genes involved in brain development, such as MCPH1 and ASAH1 [Evans et al, ; Kim and Satta, ].…”
Section: Discussionmentioning
confidence: 90%
“…Nonetheless, introgression and selection are not mutually exclusive, as a haplotype introduced by admixture may have higher chances to be detected in modern populations when subjected to a selective event (that opposes its chances of being lost by drift). This has been shown to be the case for other genes involved in brain development, such as MCPH1 and ASAH1 [Evans et al, ; Kim and Satta, ].…”
Section: Discussionmentioning
confidence: 90%
“…This approach has been used in a variety of studies during the past decade (Harris and Hey 1999; Jaruzelska et al 1999; Yu et al 2002; Barreiro et al 2005; Hayakawa et al 2006; Yotova et al 2007). To provide statistical evidence of population structure, some authors have also tested assumptions of panmixia directly using customdesigned coalescent simulations (Garrigan et al 2005a; Kim and Satta 2008). In particular, Kim and Satta (2008) tested 22 sets of demographic parameters to examine models of panmixia, bottlenecks, expansions, and population structure (both ancient and recent) for an 11kb region of the ASAH gene and found that a model of ancient structure in Africa best explained their data.…”
Section: Modeling Demographic Historymentioning
confidence: 99%
“…In parallel to the allele frequency based analyses described above, we conducted tests based on haplotype similarity. We first followed the reasoning outlined by Kim and Satta ( Kim and Satta 2008 ). Briefly, if a recent sweep indeed increased the allele frequency of a particular existing haplotype group, we expect that the nucleotide diversity would decrease among the haplotypes that were sweeped, but not the others.…”
Section: Resultsmentioning
confidence: 99%